2013
DOI: 10.1007/s00204-013-1015-7
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and carcinogenicity of the light emitted by artificial illumination systems

Abstract: The light delivered by artificial illumination systems, and in particular by halogen quartz bulbs, contains UVA, UVB, and UVC radiation, is genotoxic to both bacterial and human cells and is potently carcinogenic to hairless mice. Since IARC has classified UV radiation in Group 1, any source of UV light poses a carcinogenic hazard to humans. Suitable regulations would be needed in order to control the safety of the light emitted by artificial light sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The International Agency for Research on Cancer (IARC) classifies ultraviolet radiation, including all its components UV-A (400 nm – 315 nm), UV-B (315 nm – 280 nm), and UV-C (280 nm – 100 nm), as Group 1 [ 7 ]. In fact, exposure to UV rays causing sunburn has been shown to play a significant role in the development of melanoma, a dangerous form of skin cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) classifies ultraviolet radiation, including all its components UV-A (400 nm – 315 nm), UV-B (315 nm – 280 nm), and UV-C (280 nm – 100 nm), as Group 1 [ 7 ]. In fact, exposure to UV rays causing sunburn has been shown to play a significant role in the development of melanoma, a dangerous form of skin cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrated that exposure at 280 nM (UVC) to T. rubrum spores at a fluence of 0.5 J/cm 2 was germicidal [ 21 ]. Unfortunately there are obvious carcinogenic risks associated with utilising UVC radiation [ 22 ] and as a result we suggested that a more appropriate use of UVC could be in the decontamination of patient shoes, which represent potential reservoirs of re-infection.…”
Section: Introductionmentioning
confidence: 99%